Evolution and conduct of the meander “curva el conejo” of magdalena river in the Dorada-Caldas zone - Castañeda, Jorge Abel; Osorio, Jose Henry (Scientia et Technica, 2018)
A multitemporal analysis of the Magdalena River was carried out in the Municipality from La Dorada-Caldas, to obtain a basic model of the evolution of the channel of this drainage in the El Conejo curve. A historical count was made between the years 1924 and 2016, using tools S.I.G. The Magdalena River in the curve El Conejo of this locality, has undergone an abrupt behavior of approximately 1540 meters; Atypical in the evolution of its channel, evidenced mainly in a period between the years 1952 and 1962.